Genome wide assessment of mRNA in astrocyte protrusions by direct RNA sequencing reveals mRNA localization for the intermediate filament protein nestin. Issue 11 (5th September 2013) - Thomsen, Rune; Pallesen, Jonatan; Daugaard, Tina F.; Børglum, Anders D.; Nielsen, Anders L.
<x xml:space="preserve">Abstract</x> Subcellular RNA localization plays an important role in development, cell differentiation, and cell migration. For a comprehensive description of the population of protrusion localized mRNAs in astrocytes we separated protrusions from cell bodies in a Boyden chamber and performed high‐throughput direct RNA sequencing. The mRNAs with localization in astrocyte protrusions encode proteins belonging to a variety of functional groups indicating involvement of RNA localization for a palette of cellular functions. The mRNA encoding the intermediate filament protein Nestin was among the identified mRNAs. By RT‐qPCR and RNA FISH analysis we confirmed Nestin mRNA localization in cell protrusions and also protrusion localization of Nestin protein. Nestin mRNA localization was dependent of Fragile X mental retardation syndrome proteins Fmrp and Fxr1, and the Nestin 3'‐UTR was sufficient to mediate protrusion mRNA localization. The mRNAs for two other intermediate filament proteins in astrocytes, Gfap and Vimentin, have moderate and no protrusion localization, respectively, showing that individual intermediate filament components have different localization mechanisms. The correlated localization of Nestin mRNA with Nestin protein in cell protrusions indicates the presence of a regulatory mechanism at the mRNA localization level for the Nestin intermediate filament protein with potential importance for astrocyte functions during brain development and maintenance. GLIA 2013;61:1922–1937